Understanding human arm stiffness modulation in overground pHRI: The roles of kinematics, perturbation, and trunk sway - Mohsen Mohammadi Beirami; Sambad Regmi; Devin Burns; Yun Seong Song (PLoS ONE, 2026)
This study examines human arm kinematics during overground physical human-robot interaction (pHRI). Previous work showed humans adjust arm stiffness with changing trajectory uncertainty, but the roles of arm kinematics and muscle activation remained unclear. Building on a preliminary study, we analyzed arm movements with more participants (10 individuals) to achieve more reliable findings and examined two potential influences that arose in the preliminary study: the robot’s perturbation effect (a brief hand push) and left-to-right trunk sway. Using a linear mixed-effects model, we evaluated the effects of participant, block, and trajectory condition on arm angles. Results showed minimal kinematic contribution to stiffness modulation, with inconsistent significance levels in the measured metrics. Perturbation presence also had no significant impact on voluntary posture, with the exception of the posture differences before and after the perturbation. Trunk sway was strongly correlated with elbow angle, with a mean correlation ( R 2 ) of 0.65 and a standard deviation of 0.24. Most variability arose from individual differences rather than experimental conditions. These findings might potentially allow for more flexible mechanical design in assistive and rehabilitation robots.